Interventional cardiology during the COVID-19 epidemic - Weich, Hellmuth; Hitzeroth, Jens; Khan, Sajidah; Kettles, David; Vachiat, Ahmed; Ntsekhe, Mpiko (SA Heart Journal, 2020)
The impact of the COVID-19 pandemic on our lives is unprecedented and major adjustments to our practices as physicians are required. Although our comments are applicable at the time of writing, the situation changes daily and the content of this article should be adjusted accordingly. Cath lab: An unambiguous cath lab protocol should be drawn up for each facility, appropriate to local circumstances. This should include standard procedures in preparation for arrival at the lab, in the performance of procedures, and, importantly, in maintaining due diligence when removing protective gear. All team members should be well trained in these procedures. Acute coronary syndromes: Standard timing for the invasive management of patients should not change during the pandemic. Due to delays often unavoidable during the pandemic, alternative strategies such as thrombolysis may be more readily available and therefore more appropriate. Drugs: The sick COVID-19 patient often represents a pro-thrombotic state and operators should ensure adequate anti-thrombotic therapy. Knowledge of interactions between cardiac drugs and investigational antiviral treatments is important. Elective procedures: Patients with chronic cardiac conditions are at high risk and may require non-urgent procedures to avert major complications. Selecting these cases requires consideration of multiple risks and benefits.